Penerapan Model Pembelajaran Langsung dengan Media Komik untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Kelas III SD Negeri 006 Pangkalan Indarung Kecamatan Singingi - Marhalim, Marhalim (GERAM: Gerakan Aktif Menulis, 2017)
Teaching and learning process was basically a communication process between teacher as courier of message while student as recipient. The message, delivered by the teacher, was actually the learning materials that had been changed into communication symbol, verbally and non verbally. Indonesian languange held the important role in students’ intelectual, sosial, and emotional development and also the supporting success in learning all subjects. The learning result could be seen from how many students could pass subjects’ minimum score. A low learning result in Indonesia languange subject should be a consideration for learning planner. To improve students learning result, teacher made enhancement. One of the methods could be used for enhancement was using comic in Indonesian language subject so it couold create a condusive condition. Conducive condition was a condition where students engaged to the learning process and they were active during teaching-learning process. Indonesian language comic was interesting for them especially the pictures on it. The most important thing that students (with the help of teacher) could construct knowledge and also got so many producers and they could solve the problem given. After the treatment was given, the learning result was satisfied where 18 out of 22 students (81,8%) passed, while the rest of them did not pass yet. The students who did not pass were the students with low ability and not really active in class.